Problems of obtaining state support for a film creation project - Yu. V. Vorontsova (Вестник университета)
The Russian cinematography industry is characterized by a significant degree of dependence on state financial support. The world cinematography has a high level of quality and acts as an independent commercial mechanism that annually shows progress in the field of technologies used in the industry. It undoubtedly increases the cost of film production and sets a high level for competitors. The producer’s activity is impossible without finding financing for a project, and in most cases, the Russian government helps film companies in this matter. The problem of the described process is imperfection of the mechanisms established by the state. Therefore, the purpose of the study is to analyze the problems of obtaining state funding when creating a film project. The article is relevant due to the strong long-term interaction of the state and film production industry. Problems in the current system of state support have been identified and recommendations for their solution provided. In addition, a number of opportunities and changes that will contribute to improving competitiveness and development of domestic cinema have been considered. The article proposes to carry out reforms in the activities of the government agencies supporting the industry and to draw their attention to the development of society and human resources by improving the field of film education.